Glucose and Fructose Fermentation by Wine Yeasts in Media Containing Structurally Complex Nitrogen Sources - Miranda Junior, Messias [UNESP]; Batistote, Margareth [UNESP]; Ernandes, Jose Roberto [UNESP] (Inst Brewing, 2008)
Glucose and fructose fermentations by industrial yeasts strains are strongly affected by both the structural complexity of the nitrogen Source and the availability of oxygen. In this Study two Saccharomyces cerevisiae industrial wine strains were grown, under shaken and static conditions, in a media containing either a) 20% (w/v) glucose, or b) 10% (w/v) fructose and 10% (w/v) glucose or c) 20% (w/v) fructose, all supplemented with nitrogen Sources varying from a single ammonium salt (ammonium Sulfate) to free amino acids (casamino acids) and peptides (peptone). Data Suggest that 1 complex Structured nitrogen source is not submitted to the same control mechanisms as those involved in the utilization of simpler structured nitrogen Sources, and mutual interaction between carbon and nitrogen Sources, including the mechanisms involved ill the regulation of aerobic/anaerobic metabolism, may play in important role in defining yeast fermentation performance and the differing response to the structural complexity of the nitrogen Source, with a strong impact oil fermentation performance.
Keywords: Amino acids; anaerobiosis; fermentation; fructose utilization; glucose utilization; nitrogen metabolism; peptides; Saccharomyces; stuck fermentation; wine yeasts